Childcare sharing and family happiness: analyzing parental and child well-being in the actor-partner interdependence model - Young-Eun Lee (Frontiers in Public Health, 2024)
IntroductionThe exploration of the relationship between parental and child happiness, particularly in the context of shared childcare responsibilities, has not been examined in Korean families.MethodsUsing a two-wave longitudinal design and data from 1,403 families from the Panel Study on Korean Children, this study employed the actor-partner interdependence model to examine the dynamics of childcare sharing between mothers and fathers in South Korea.ResultsMothers’ childcare sharing was found to have no significant impact on their own and their partner’s happiness, reflecting traditional gender norms that undervalue mothers’ contributions. In contrast, fathers’ childcare sharing had a positive impact on their own and their spouse’s happiness, suggesting a growing recognition of fathers’ involvement. Furthermore, fathers’ active participation in childcare was found to promote their children’s happiness through their own happiness.DiscussionThis study reflects the complexity of evolving family roles and the covert persistence of traditional gender roles in modern Korean parenting. It suggests the importance of work and family policies that support changes in family dynamics by providing a more nuanced understanding of how changing family roles and responsibilities can enhance overall family well-being.